Pengembangan permainan kecil pada materi lari jarak pendek - Utama, Sari Fitri; Kristina, Putri Cicilia; Lubis, Patricia H. M (Universitas Hamzanwadi, 2023)
The problem in this research departs from the students' need for games in learning to run short distances. The aim of the research was to find out the development of a game on short distance running material that is valid and practical for fifth grade elementary school students. The research method is a research and development method with the ADDIE stage model consisting of analysis, design, development, implementation and evaluation. Product validity involves game experts, learning experts and media experts. The practicality test used fifth grade students at SD Negeri 85 Prabumulih. Data is collected through a questionnaire. Data analysis using percentage analysis. The results of the study stated that the small game model on distance running material for fifth grade elementary school students was valid to use because the average validation value was 90.06. The small game model on distance running material for fifth grade students of the Practical Elementary School is used because the user's perception value is 82.63%. In conclusion, the practicality of the product from 22 students using the small game model product on short-distance running material for elementary school students was stated to be practically used by students as a game medium.